The correlation between satisfaction of the value added services and customer loyalty of Banglalink Digital Communication Ltd. - Sultana, Razia (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.